The Impact of Providing Mycorrhiza and Palm Oil Waste Planting Media on the Growth of Shallot Plants (Allium ascalonicum) - Rahmania, Rahmania (Biofarm : Jurnal Ilmiah Pertanian, 2024)
Improving shallot cultivation techniques needs to be done by providing mycorrhiza and palm oil waste as a mixture of planting media for shallot growth and production. The aim of this experiment was to determine the effect of mycorrhiza, planting media, the interaction of providing mycorrhiza and shallot production in this research using a Randomized Block Design with a factorial pattern. The first factor is mycorrhizal inoculation consisting of three levels: no mycorrhizal inoculation, 50 and 100 grams of mycorrhizal inoculant/plant. The second factor is the planting media with four levels of planting media: Top soil, Top soil + EFB (1:1), top soil + fiber (1:1), and Top soil + mud (1:1). The research results showed that growing media had a significant effect on the number of shallot leaves. Top soil + mud planting media is the best treatment for growth and. Providing mycorrhiza, the interaction of providing mycorrhiza and planting media did not have a significant effect on plant height and number of shallot seedlings